Sliding wear resistance of porous biomorphic sic ceramics. (September 2016) - López-Robledo, M.J.; Gómez-Martín, A.; Ramírez-Rico, J.; Martínez-Fernández, J.
Abstract: Porous biomorphic SiC ceramics were fabricated from four different wood precursors, three natural woods and one recycled wood product, by reactive infiltration of molten silicon into a carbon preform obtained from wood pyrolysis. Sliding wear resistance when sliding against a Si3 N4 ball in air was studied. Tribological experiments were done with a pin-on-disk apparatus, under normal loads of 1 and 2 N, at a sliding velocity of 100 mm/s. The wear properties and the volume fraction of porosity were correlated. A commercial sintered SiC ceramic was also tested for comparison. The measured values of friction coefficient were in the range reported in literature for monolithic SiC ceramics under similar dry contact conditions. Two concurrent wear mechanisms are taking place: abrasion from the SiC debris and soft ploughing. The presence of an oxide tribolayer was assessed using energy dispersive X-ray analysis. Wear rates were found to scale with the composite porosity. Highlights: Porous biomorphic SiC ceramics were fabricated from four different wood precursors. Sliding wear resistance of porous bioSiC was studied. Measured friction coefficients are comparable to monolithic SiC. Abrasion from the SiC debris and soft ploughing are the concurrent wear mechanisms. Tribo-oxidation also contributes to overall wear.